2022
DOI: 10.1002/ptr.7643
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of integrated traditional Chinese and Western medicine against COVID‐19: A systematic review and meta‐analysis

Abstract: Although plenty of clinical trials have confirmed the efficacy and safety of integrated traditional Chinese and Western medicine (ITCWM) against COVID-19, the role of ITCWM remains controversial. So we conducted a systematic review and metaanalysis of published studies in eight major databases that report the outcomes of interest in COVID-19 patients receiving ITCWM. RevMan5.4 software was used for meta-analysis, while the quality of RCTs was assessed by the Cochrane risk of bias tool and the retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(91 reference statements)
2
7
0
Order By: Relevance
“…The statistical analysis of the data revealed that ITCWM demonstrated signi cantly better outcomes compared to Western medicine alone, showing higher overall clinical effectiveness. These ndings are consistent with our own research, demonstrating signi cant results in terms of overall clinical effectiveness, faster fever resolution, quicker disappearance of cough, and faster time to RT-PCR negativity [23]. The ndings from our study coincide with the existing literature on this topic, which is suggestive of a superior effectiveness of Chinese medicine in treating patients with COVID-19, without any apparent safety concerns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The statistical analysis of the data revealed that ITCWM demonstrated signi cantly better outcomes compared to Western medicine alone, showing higher overall clinical effectiveness. These ndings are consistent with our own research, demonstrating signi cant results in terms of overall clinical effectiveness, faster fever resolution, quicker disappearance of cough, and faster time to RT-PCR negativity [23]. The ndings from our study coincide with the existing literature on this topic, which is suggestive of a superior effectiveness of Chinese medicine in treating patients with COVID-19, without any apparent safety concerns.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are supported by the work of Zhuang and colleagues [23] who in a systematic review and meta analysis (including 53 studies, n = 5,425) evaluated the e cacy and safety of integrated Chinese and Western Medicine (ITCWM) in COVID-19 patients. The statistical analysis of the data revealed that ITCWM demonstrated signi cantly better outcomes compared to Western medicine alone, showing higher overall clinical effectiveness.…”
Section: Discussionsupporting
confidence: 79%
“…The therapies highlighted in the rapid reviews conducted by the WNF in May 2020 supported the findings of the systematic reviews as of the end of 2022. That is, the most common natural therapies to consider in the prevention and treatment of COVID-19 and post-COVID include Vitamin C, 212 Vitamin D, 213 multivitamins, 214 Zinc, 215 Quercetin, 216 N-Acetyl-cysteine (NAC), 217 essential oils, 218 and the herbs Echinacea, 219 Hedera helix, 220 and Sambucus nigra. 221 Despite the mounting volume of research on natural approaches for the prevention and treatment of COVID-19, there has been limited acknowledgement by or interest from governments with respect to the role of T&CM either adjunctively or individually with respect to the prevention and/or treatment of COVID-19 and/or post-COVID.…”
Section: Growing Interest In the Role Of Nhps And Natural Therapies I...mentioning
confidence: 99%
“…How to circumvent these threats? The ancient application and contemporary research of TCM and other traditional medicine systems give us a lot of spurs (Karimi et al, 2021;Pagano, 2022;Singh et al, 2021;Zhuang et al, 2022). The specialized phytometabolites induced by stress factors vary greatly, which, along with their therapeutic efficacy, may possess phylogenetic cues (Zaman et al, 2021;Zhang et al, 2020).…”
Section: In the Direction Of The Beginning: Traditional Medicines Ill...mentioning
confidence: 99%
“…From Wuhan to Shanghai, and from the Delta variant to Omicron, China is tackling the qualms of the pandemic. Chinese herbal medicines have always been at the forefront of the battle against SARS, influenza, and COVID-19 over the years (Choi, Lee, & Chang, 2020;Liu, Zhang, He, & Li, 2012;Zhuang et al, 2022), which bear witness to the efforts and success in epidemic prevention and control.…”
mentioning
confidence: 99%